Radical reduction and reconstruction for male genital elephantiasis: Superficial circumflex iliac artery perforator (SCIP) lymphatic flap transfer after elephantiasis tissue resection. Issue 2 (February 2022) - Yamamoto, Takumi; Daniel, Bassem W.; Rodriguez, Jose R.; Kageyama, Takashi; Sakai, Hayahito; Fuse, Yuma; Tsukuura, Reiko; Yamamoto, Nana
Summary: Background: Treatment of elephantiasis, the most severe lymphedema, is challenging. Management of male genital elephantiasis (MGE) is even more challenging than extremity elephantiasis due to its complicated shape and high risk of lymphorrhea and cellulitis. Complete resection of fibrous tissue and lymphatic reconstruction is considered to be ideal for the treatment of MGE. The aim of this study was to evaluate the feasibility of radical reduction and reconstruction (3R) for isolated MGE. Methods: Medical charts of patients who underwent 3R were reviewed. The 3R operation consisted of genital fibrous tissue resection and reconstruction of soft tissue and lymphatic structure using superficial circumflex iliac artery perforator (SCIP) lymphatic flap transfer (LFT). No compression was applied postoperatively. Patient and flap characteristics, intraoperative findings, and postoperative results were evaluated. Results: Seven patients were included. MGE included isolated scrotal elephantiasis in 4 cases, and scrotal and penile elephantiasis in 3 cases. Resected tissue volume ranged from 609 to 2304 grams (average, 1511.0 grams). SCIP-LFT was performed in all cases; pedicled full-thickness SCIP-LFT for scrotal reconstruction in all cases, and SCIP pure-skin-perforator flap transfer for penile reconstruction in 3 cases. There was no postoperative genital complication or evidence of genital lymphedema recurrence in the mean follow-up period of 22.7 months. Genital lymphedema scores significantly improved postoperatively (6.7 ± 1.8 vs. 0.3 ± 0.5, P <0.001). Conclusions: 3R operation allowed one-stage curative treatment for MGE. LFT has the potential to play an essential role in the prevention of postoperative wound complications and lymphedema recurrence after radical resection of fibrotic tissue.